Nursing research landscape in Malaysia: a systematic scoping review protocol on journal publications from 2015 to 2024 - Wei Hong Lai; Andy Han Siang Lim; Monica Danial; Aina Magdalena Anak Jolly; Nurkhairunnisa Binti Norudin; Angela Sik Hui Eu; Anthiana Martina Anak Molly; Rosnah Binti Mohidin; Alex Ren Jye Kim; Siswanita Anak Main; Nor Asiah Binti Muhamad (BMJ Open)
Introduction The nursing profession has undergone significant evolution over the past century, shifting from a role traditionally viewed as an auxiliary to physicians to one of autonomous healthcare professionals equipped with specialised skills and expertise. This shift is driven by the increasing recognition of the importance of evidence-based practice in enhancing patient outcomes and advancing the field of nursing. Consequently, nursing research has emerged as a critical priority in the profession. This study seeks to explore the nursing research landscape in Malaysia, where data remain limited, by examining trends before, during and after the COVID-19 pandemic.Methods and analysis This scoping review will be conducted following the Arksey and O'Malley framework, using four electronic databases: PubMed, Scopus and CINAHL for journal articles published between 2015 and 2024, and Web of Science for conference proceedings from the same period.Ethics and dissemination The findings from this scoping review will provide an overview of the nursing research landscape in the Malaysian context, offering insights that could guide the future advancement of nursing research in the country. The results will be disseminated through submission to a peer-reviewed scientific journal for publication. Ethical approval is not required for this scoping review, as it involves the synthesis of data from available published literature.